An Analysis of Using Chuchu TV Nursery Rhymes and Kids Songs YouTube Channel as Medium for Learning Early Childhood English Vocabulary - Peni Maulita; Suhono Suhono; Rizky Hidayatullah; Yeasy Agustina Sari (CV. Creative Tugu Pena, 2022)
Many children who have not been able to master basic English vocabulary such as various colors, animals, fruits, and the alphabet Learning English must be done from an early age, one of the media that can be used to learn English is YouTube. YouTube is an interesting medium to use in the teaching and learning process of English. YouTube users are spread all over the world from various age groups, from early childhood to adults. One of the popular YouTube Channels among children is ChuChu TV. This study aims to analyze the use of ChuChu TV as a vocabulary-learning medium for early childhood. This research is a type of qualitative research with a case study method. Researchers used observation and interviews as data collection techniques. Participants in this study were children aged 5 to 6 years in Purwosari, North Metro District, Metro City. The research results show that the use of the ChuChu TV YouTube Channel can improve English vocabulary in some early childhood students. Keywords: English Vocabulary, YouTube Education, Early Childhood